Exploring programme design, evaluation of programme performance and describing the clinical outcomes of a public sector based ARV treatment programme in a semi-rural area in the Western Cape over the past 6 years. (2004-2010) - Grobbelaar, Cornelis Johannes (Nelis) (Stellenbosch : Stellenbosch University, 2013)
Thesis (MFamMed)--Stellenbosch University, 2012.